Synthesis, Physical Characterization and Biological Evaluation of Schiff BaseCr(III), Mn(III) and Fe(III) Complexes. Issue 3 (2010) - Kumar, Gajendra; Kumar, Dharmendra; Devi, Shoma; Kumar, Amit; Johari, Rajeev
Abstract : M(III) complexes with Cr, Mn and Fe with Schiff base derived from 2-amino-4-ethyl-5-hydroxy benzaldehyde and oxocarbohydrazide were synthesized and characterized by several techniques using elemental analysis (C, H, N), molar conductance measurements, magnetic measurements, electronic, mass and IR spectral studies. On the bases of these studies, a five coordinated square pyramidal geometry for all these complexes has been proposed and found to be potential antimicrobial agent. The Schiff base ligand and complexes were also tested for their antimicrobial activity (against the bacteria Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Bacillus megaterium and the fungi Kluyveromyces fragilis, Rhodotorula rubra, Candida albicans and Trichoderma reesei ) to assess their inhibiting potential. An attempt is also made to correlate the antimicrobial activity with geometry of the complexes. All complexes were found to be less active against the pathogens E.coli, S.aureus and P.aeruginosa . Cr(III) complex showed the best antimicrobial activity, but ligand alone was found to be active against the fungus T.reesei .